Changes and thresholds in the Forgotten Joint Score after total hip arthroplasty: minimal clinically important difference, minimal important and detectable changes, and patient-acceptable symptom state. (1st December 2021) - Robinson, Patrick G.; MacDonald, Deborah J.; Macpherson, Gavin J.; Patton, James T.; Clement, Nick D.
Abstract : Aims: The aim of this study was to identify the minimal clinically important difference (MCID), minimal important change (MIC), minimal detectable change (MDC), and patient-acceptable symptom state (PASS) in the Forgotten Joint Score (FJS) according to patient satisfaction six months following total hip arthroplasty (THA) in a UK population. Methods: During a one-year period, 461 patients underwent a primary THA and completed preoperative and six-month FJS, with a mean age of 67.2 years (22 to 93). At six months, patient satisfaction was recorded as very satisfied, satisfied, neutral, dissatisfied, or very dissatisfied. The difference between patients recording neutral (n = 31) and satisfied (n = 101) was used to define the MCID. MIC for a cohort was defined as the change in the FJS for those patients declaring their outcome as satisfied, whereas receiver operating characteristic curve analysis was used to determine the MIC for an individual and the PASS. Distribution-based methodology was used to calculate the MDC. Results: Using satisfaction as the anchor, the MCID for the FJS was 8.1 (95% confidence interval (CI) 3.7 to 15.9; p = 0.040), which was affirmed when adjusting for confounding. The MIC for the FJS for a cohort of patients was 17.7 (95% CI 13.7 to 21.7) and for an individual patient was 18. The MDC90 for the FJS was eight, meaning that 90% of patients scoring more than this will have experienced a real change that is beyond measurement error. The PASS threshold for the FJS was defined as 29. Conclusion: The MCID and MIC can be used respectively to assess whether there is a clinical difference between two groups, or whether a cohort or patient has had a meaningful change in their FJS. Both values were greater than measurement error (MDC90), suggesting a real change. The PASS threshold for the postoperative FJS can be used as a marker of achieving patient satisfaction following THA. Cite this article: Bone Joint J  2021;103-B(12):1759–1765.